2009
DOI: 10.1214/08-aoas215
|View full text |Cite
|
Sign up to set email alerts
|

Network exploration via the adaptive LASSO and SCAD penalties

Abstract: Graphical models are frequently used to explore networks, such as genetic networks, among a set of variables. This is usually carried out via exploring the sparsity of the precision matrix of the variables under consideration. Penalized likelihood methods are often used in such explorations. Yet, positive-definiteness constraints of precision matrices make the optimization problem challenging. We introduce non-concave penalties and the adaptive LASSO penalty to attenuate the bias problem in the network estimat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
367
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 318 publications
(369 citation statements)
references
References 32 publications
1
367
0
1
Order By: Relevance
“…We follow arguments similar to those given by Fan, Feng, and Wu (2009) to prove Theorems 2 and 3. However, one cannot directly apply Fan et al's results here, because the parameters must satisfy the acyclicity constraint, the data we have are not iid observations due to interventions, and the identifiability of a DAG is not always guaranteed.…”
Section: Theorem 1 Suppose That Xmentioning
confidence: 99%
“…We follow arguments similar to those given by Fan, Feng, and Wu (2009) to prove Theorems 2 and 3. However, one cannot directly apply Fan et al's results here, because the parameters must satisfy the acyclicity constraint, the data we have are not iid observations due to interventions, and the identifiability of a DAG is not always guaranteed.…”
Section: Theorem 1 Suppose That Xmentioning
confidence: 99%
“…Several future research topics have been indicated, including analyzing the asymptotic property of the CSSL problem (8), and extending the current formulation to the adaptive Lasso (Zou, 2006;Fan et al, 2009) type one to guarantee the oracle property (Zou, 2006) of the estimator. Applying the notion of commonness to more general dependency models, such as those with non-linear relations or commonness based on higher-order moment statistics, is also important.…”
Section: Resultsmentioning
confidence: 99%
“…Once they are obtained, ∆u, ∆Z can be obtained from (12) and the first equation of (10), respectively. After that, ∆x 1 , ∆x 2 can be computed from (11).…”
Section: An Inexact Primal-dual Interior-point Methodsmentioning
confidence: 99%
“…Once ∆y, ∆u are computed, ∆Z can be obtained from the first equation of (10), while ∆x 1 , ∆x 2 can be computed from (11). The unknown ∆X is easy to obtain since from the fourth equation of (10), we have…”
Section: An Inexact Primal-dual Interior-point Methodsmentioning
confidence: 99%
See 1 more Smart Citation